«Наш цісар». Образ Франца Йосифа в львівській пресі – еволюція від «переможця над повстанцями» 50-их років ХІХ століття до «доброго батька» початку ХХ століття - Кісь, Назар (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Artykuł analizuje zmiany wizerunku cesarza Franciszka Józefa I na łamach lokalnej prasy lwowskiej. Za punkt odniesienia przyjęto wizyty Franciszka Józefa we Lwowie. Było ich pięć i pozwalają one prześledzić przemianę od monarchy absolutnego połowy XIX wieku do „naszego ojca” na początku XX wieku. W tekście ukazano jak postęp gospodarczy i technologiczny, liberalne reformy, emancypacja, rozwój projektów narodowych Ukraińców i Polaków, a także inne osiągnięcia drugiej połowy XIX wieku, wpłynęły na kształt osobistej historii cesarza, który nawet w czasach szerzenia się nacjonalizmu, uosabiał państwo i ojczyznę – ziemię, na której panują Habsburgowie.

The article analyzes the changes in the image of Emperor Franz Joseph I as depicted in the local Lviv press. The visits of Franz Joseph to Lviv serve as a reference point for this analysis. There were five visits in total, which allow tracing the transformation of the monarch from an absolute ruler in the mid-19th century to the “father figure” at the beginning of the 20th century. The text highlights how economic and technological progress, liberal reforms, emancipation, the development of national projects by Ukrainians and Poles, as well as other achievements of the second half of the 19th century, influenced the personal history of the emperor. Even in times of growing nationalism, he personified the state and the homeland – the land ruled by the Habsburgs.
„Nasz cesarz”. Wizerunek Franciszka Józefa w prasie lwowskiej. Ewolucja od „zwycięzcy buntowników” z lat 50. XIX wieku do „dobrego ojca” początku XX wieku
“Our Emperor”. The image of Franz Joseph in the Lviv press. Evolution from “the rebel victor” of the 1850s to “the good father” of the early 20th century
Keywords: Franciszek Józef; cesarz; wizyta; rytuał; wizerunek; Franz Joseph; emperor; visit; ritual; image